Star Wars: Revenge of the Sith - George Lucas (2026)
Star Wars; Revenge of the Sith is a 2005 American epic space opera film written and directed by George Lucas. It is the third installment of the Star Wars prequel trilogy and stars Ewan McGregor Natalie Portman Hayden Christensen Ian McDiarmid Samuel L. Jackson Christopher Lee Anthony Daniels Kenny Baker and Frank Oz. It is the sixth film in the Star Wars franchise.